#cutting: Non-suicidal self-injury (NSSI) on Instagram. Issue 2 (14th July 2017) - Brown, R. C.; Fischer, T.; Goldwich, A. D.; Keller, F.; Young, R.; Plener, P. L.
Abstract : Background: Social media presents an important means for social interaction, especially among adolescents, with Instagram being the most popular platform in this age-group. Pictures and communication about non-suicidal self-injury (NSSI) can frequently be found on the internet. Methods: During 4 weeks in April 2016, n = 2826 (from n = 1154 accounts) pictures which directly depicted wounds on Instagram were investigated. Those pictures, associated comments, and user accounts were independently rated for content. Associations between characteristics of pictures and comments as well as weekly and daily trends of posting behavior were analyzed. Results: Most commonly, pictures depicted wounds caused by cutting on arms or legs and were rated as mild or moderate injuries. Pictures with increasing wound grades and those depicting multiple methods of NSSI generated elevated amounts of comments. While most comments were neutral or empathic with some offering help, few comments were hostile. Pictures were mainly posted in the evening hours, with a small peak in the early morning. While there was a slight peak of pictures being posted on Sundays, postings were rather evenly spread across the week. Conclusions: Pictures of NSSI are frequently posted on Instagram. Social reinforcement might play a role in the posting of more severe NSSI pictures. Social media platforms need to take appropriate measures for preventing online social contagion.